Analisis Pengelolaan Dana Desa dalam Meningkatkan Perekonomian Masyarakat di Desa Moncongloe Lappara - Usman; Bachtiar; Hasran (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2024)
This research aims to find out how village fund management increases the economy of people in the village of The Moncongloelappara Subdistrict Snout Regency Maros. And to find out the effort of the government village to increase the economy through village fund management in the village monopole lappara Subdistrict Snout Regency Maros. This research uses a descriptive qualitative type of study. In author data collection use technique observation, interview deep, and studies library. Results This study shows that Fund Management Village so far it has been working effectively so far. However,​ The allocation is not 100% effective. Village fund management is said to have been effective because it can be reviewed from the field that has proof that is in the form of development infrastructure, and empowerment in the field of general And religious. Reviewed from economy so village fund management is not yet complete going well. Efforts​ government to increase the economy public namely by empowerment among others in the field of infrastructure, empowerment, field general And religious. Empowerment on field infrastructure is with the existence of making ditches, roads, construction nets fish or nets, And making cakes as well as embroidery. For empowerment public in the field general And religious. In the field generally realized by the existence of PKK. In the field of religion realized by holding religious studies routine And training tahyizmayit.